The impact of intensive management on pain intensity in patients with rheumatoid arthritis and psoriatic arthritis: secondary analysis of three clinical trials - Fowzia Ibrahim; David L. Scott; Ian C. Scott (BMC Rheumatology)
Abstract Background Understanding the impact of intensive treatment on pain in patients with rheumatoid arthritis (RA) and psoriatic arthritis (PsA) is crucial to informing the application of evidence-based arthritis pain care. The impact of intensive treatment on inflammatory arthritis pain has received relatively limited attention. We addressed this through a detailed secondary analysis of three trials evaluating varying intensities of disease-modifying anti-rheumatic drug treatment. We considered a range of pain outcomes of clinical relevance to patients, including the achievement of mild endpoint pain scores and clinically-meaningful pain reductions. Methods The trials comprised MIPA in PsA, CARDERA in early RA, and TITRATE in established RA. Pain was measured using a 100-mm pain intensity visual analogue scale (VAS). The impact of intensive treatment on (a) patients achieving “mild” endpoint pain intensity scores (of ≤ 34), b) mean changes in pain intensity scores, and (c) patients achieving ≥ 30% reductions in pain intensity scores was evaluated using t-tests, chi-squared tests, and regression models (with the latter adjusting for relevant potential confounding variables). Results From MIPA, CARDERA, and TITRATE 128, 379, and 258 patients had endpoint outcome data available and were included in this secondary analysis. In all trials, significantly more patients achieved mild endpoint pain intensity scores with intensive vs. control treatment (MIPA 70% vs. 42%, P = 0.003; CARDERA 71% vs. 56%, P = 0.011; TITRATE 67% vs. 50%, P = 0.008). In the two trials employing the most intensive management strategies (CARDERA; TITRATE) overall reductions in pain scores were significantly greater (6.6 to 6.8 units in adjusted linear regression models), and significantly more achieved ≥ 30% reductions in pain with intensive vs. control treatment (adjusted logistic regression models: CARDERA odds ratio [OR] 1.9, P = 0.009; TITRATE OR 2.2, P = 0.002). Conclusions Intensive treatment is an important component of improving pain in patients with active RA and PsA. Our findings support EULAR guidance that optimising disease activity is crucial for pain control. As approximately one third of patients receiving active treatment had moderate/high endpoint pain intensity levels across trials, additional pain management strategies that complement intensive treatment are needed. Trial registration Current Controlled Trials CARDERA ISRCTN32484878 (25/10/2000), MIPA ISRCTN54376151 (04/02/2002), and TITRATE ISRCTN70160382 (16/1/2014).